Evading Detection: Characteristics of Individuals With Extrafamilial Child Sexual Offences and Long Detection Lags - Nicol, Samuel J. (International journal of offender therapy and comparative criminology, 2024)
Most child sex offending is unreported and undetected. Despite this, most research relies on the characteristics of those frequently detected and arrested. This study aims to address this disparity by examining a group of men convicted of child sexual abuse (CSA) offences with multiple victims and who evaded detection for long periods of time (n = 170). This sample was compared to a group of men caught quickly for CSA offences against multiple victims (n = 170). The two groups were compared on demographic, lifestyle, sexual deviancy, and criminogenic measures. Individuals with long detection lags had more child victims, including more pre-pubescent and male victims and commenced their sexual offending at a comparatively earlier age. Additionally, individuals with long detection lags were more likely to be non- Indigenous and to show specialization in their sexual offending. These findings have implications for identifying and managing high harm child sexual offenders who evade detection for long periods.